Outbreak of recombinant lumpy skin disease virus in yaks: high mortality and systemic pathogenesis in Qinghai-Tibet Plateau yak herds - Jianwu Hu; Jianwu Hu; Yan Li; Xiaohu Zhang; Yaozhong Lu; Zhibo Zeng; Mengen Xu; Siyang Mou; Shah Nawaz; Dongjing Wang; Tianwu An; Xiaowei Li; et al. (Frontiers in Veterinary Science)
The emergence of recombinant Lumpy Skin Disease Virus (LSDV) strains in Asia has led to outbreaks marked by severe skin nodules, high transmissibility, and transboundary spread, resulting in significant economic losses to cattle industries in China and neighboring countries. The Qinghai-Tibet Plateau, historically a natural barrier against viral incursions, has recently experienced increasing LSDV cases in yaks (Bos grunniens). Current study elucidates the threat posed by recombinant LSDV strains to yaks through clinical, pathological, and molecular analyses. Field observations revealed infected yaks exhibited fever, dyspnea, cutaneous pox lesions, lymphadenopathy, and mucosal lesions. Viral DNA detection showed 100% positivity in skin samples (6/6), 53.33% (8/15) in nasal swabs, and 33.33% (5/15) in anal swabs, with an overall mortality rate of 46.67% (7/15). Necropsy identified respiratory and digestive system lesions, including tracheal congestion, pulmonary hemorrhagic plaques, and ruminal serosal hemorrhagic masses. Histopathology demonstrated dermal vasculitis, lymphocytic infiltration, and viral inclusion bodies. Immunohistochemistry localized viral antigens to hair follicle epithelia and macrophages. Phylogenetic analysis positioned the yak-derived LSDV strain (LSDV/China/GS/Yak) within the Cluster 1.2 recombinant subclade with high homology to recombinant strains circulating in East/Southeast Asia but differing from non-recombinant Indian Cluster 1.2 strains. The results emphasize increased pathogenicity of recombinant LSDV in plateau yaks and convey the critical need for region-specific control strategies.